Korupsi Politik, Hukum dan Etika: Diskursus Kegaduhan di Tengah Panggung Demokrasi Indonesia - Muammar, Muammar; Taufik, Iqbal; Saimima, Judy Marria (MATAKAO Corruption Law Review, 2024)
Introduction: The recent 2024 elections have left so many interesting issues and become public investigations. Such as the issue of violations of the law, violations of ethics, even leading to the issue of political corruption. These issues are so interesting, that almost every day the news in various media only contains them. Purposes of the Research: This paper aims to describe and analyze how the correlation between political, legal and ethical corruption issues and is rife during the 2024 election. Methods of the Research: This paper uses normative legal research methods. The approach used is a conceptual approach and a statutory approach. Results of the Research: The occurrence of various events that colored the implementation of the 2024 elections has captured public attention and energy so far. Various kinds of violations of law and ethics are presented and displayed in front of the public eye. The discourse on political corruption came to the fore along with the performance "attracted" by President Joko Widodo. Starting from "cawe-cawe" (interfering) in political affairs to the issue of intervention in various policies, including the alleged birth of the Constitutional Court decision No.90/PUU-XXI/2023. In addition, various issues of violations of law and ethics also "flooded" the 5-year political event. Even during almost the entire implementation of the 2024 elections, the issue of violations of law and ethics takes a significant portion. The correlation between the two is very close and inseparable. Law is like packaging that wraps the ethics that are the contents of the packaging. In that position, ethics occupies a "special" position because it actually originates from the moral niche of man, where law in the sense of norms has no such thing.